2016
DOI: 10.1002/hbm.23198
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectome disruption at baseline predicts 6-months post-stroke outcome

Abstract: In this study, models based on quantitative imaging biomarkers of post-stroke structural connectome disruption were used to predict six-month outcomes in various domains. Demographic information and clinical MRIs were collected from 40 ischemic stroke subjects (age: 68.1±13.2 years, 17 female, NIHSS: 6.8±5.6). Diffusion-weighted images were used to create lesion masks, which were uploaded to the Network Modification (NeMo) Tool. The NeMo Tool, using only clinical MRIs, allows estimation of connectome disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 83 publications
1
100
0
Order By: Relevance
“…However, disconnections can occur at any segment along WM tracts, and, consequently, lesions apparently unrelated to each other can cause disruption of the same tract, producing similar symptoms. Supporting this rationale, recent studies have shown that structural disconnections can predict cognitive performance more accurately than lesion location [Hope et al, ; Kuceyeski et al, ]. Nonoverlapping lesions can also affect the same functional network, leading to similar clinical syndromes [Boes et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, disconnections can occur at any segment along WM tracts, and, consequently, lesions apparently unrelated to each other can cause disruption of the same tract, producing similar symptoms. Supporting this rationale, recent studies have shown that structural disconnections can predict cognitive performance more accurately than lesion location [Hope et al, ; Kuceyeski et al, ]. Nonoverlapping lesions can also affect the same functional network, leading to similar clinical syndromes [Boes et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Yourganov et al [] created predictive models of several aphasia scores from 90 subjects using either lesion or structural connectivity information, and achieved correlation scores in the range r = 0.52–0.72. In another study, Kuceyeski et al [] predicted future cognitive abilities in post‐stroke subjects using virtual tractography lesions, achieving an accuracy of r = 0.75. Compared to the above literature, STAMP showed higher predicted vs. true correlation ( r = 0.79–0.88) by integrating multimodal information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A traditional lesion overlap analysis showed these patients had largely non-overlapping damage; however, lesion-network mapping demonstrated that the patients who were impaired on the IGT showed overlap in their lesion connectivity maps with somatosensory, motor and insula cortices, to a greater extent than patients who had unimpaired performance on the IGT. An analogous approach utilizing diffusion tractography imaging (DTI) data has also shown promise in understanding outcome from stroke (Kuceyeski et al, 2016). Future refinements to these network-derived lesion-mapping approaches (for example, combining DTI and resting-state data) hold further promise for better appreciating the remote effects of damage in the context of neuropsychological studies of brain and behavior.…”
Section: Predictions About Further Advancesmentioning
confidence: 99%